The effect of "Rheoambrasol" on morphological changes in the liver and kidneys in nitrite methemoglobinemia - Ibragimov M. N.; Khaidarov A. K.; Shevchenko L. I.; Khakimova D. Z.; Khuzakhmedov J. D.; Alimov T. R. (BIO Web of Conferences, 2023)
We propose a new drug - "Rheoambrasol" which includes a substance of plant origin (complex compounds of polysaccharide and natural metabolite) non-toxic, environmentally friendly and has wide functional capabilities as a means capable of correcting the consequences of methemoglobinemia, restoring structural and functional properties of cells and preserving their viability. The aim of the work is to study the effect of the new blood substitute "Rheoambrasol" on morphological changes in the liver and kidneys in nitrite methemoglobinemia. The treatment of nitrite methemoglobinemia with rheoambrosol shows complete disappearance of general pathological phenomena both in the liver and kidney tissue. The drug Rheoambrasol containing a natural metabolite of the Krebs cycle in combination with polysaccharides increases the activity of the liver metabolizing function in toxic liver damage. These positive histostructural changes in the liver tissue and in the kidney tissue indicate an increase in the activity of metabolic function of the liver parenchyma and a significant decrease in the toxemia index.